(untitled) (Journal of Institute of Medicine Nepal, 2011)
A 27 year old pregnant woman was prescribed conventional oral iron tablets from second trimester of pregnancy. She developed gastrointestinal symptoms within 1-2 days. Following these symptoms, Iron tablets were stopped and the patient was started with iron capsule. The patient tolerated this preparation well and after 6 months she developed yellowish discoloration of the teeth and nails. Iron treatment was suspected for the discolorations and the drug was stopped. Upon stopping the therapy the discoloration vanished and teeth and nails returned to the pre treatment condition. The causality assessment and the severity assessments were carried out as per the Naranjo and Hartwig scales respectively. Since Iron treatment during pregnancy is common, this adverse drug reaction warrants monitoring. Keywords: Iron; nail discoloration; pregnancy; teeth discoloration DOI: http://dx.doi.org/10.3126/joim.v32i2.4945 Journal of Institute of Medicine, August, 2010; 32: 44-46